The evidence underpinning sports performance products: a systematic assessment. Issue 4 (18th July 2012) - Heneghan, Carl; Howick, Jeremy; O'Neill, Braden; Gill, Peter J; Lasserson, Daniel S; Cohen, Deborah; Davis, Ruth; Ward, Alison; Smith, Adam; Jones, Greg; Thompson, Matthew
Abstract : Background: To assess the extent and nature of claims regarding improved sports performance made by advertisers for a broad range of sports-related products, and the quality of the evidence on which these claims are based. Methods: The authors analysed magazine adverts and associated websites of a broad range of sports products. The authors searched for references supporting the performance and/or recovery claims of these products. The authors critically appraised the methods in the retrieved references by assessing the level of evidence and the risk of bias. The authors also collected information on the included participants, adverse events, study limitations, the primary outcome of interest and whether the intervention had been retested. Results: The authors viewed 1035 web pages and identified 431 performance-enhancing claims for 104 different products. The authors found 146 references that underpinned these claims. More than half (52.8%) of the websites that made performance claims did not provide any references, and the authors were unable to perform critical appraisal for approximately half (72/146) of the identified references. None of the references referred to systematic reviews (level 1 evidence). Of the critically appraised studies, 84% were judged to be at high risk of bias. Randomisation was used in just over half of the studies (58.1%), allocation concealment was only clear in five (6.8%) studies; and blinding of the investigators, outcome assessors or participants was only clearly reported as used in 20 (27.0%) studies. Only three of the 74 (2.7%) studies were judged to be of high quality and at low risk of bias. Conclusions: The current evidence is not of sufficient quality to inform the public about the benefits and harms of sports products. There is a need to improve the quality and reporting of research, a move towards using systematic review evidence to inform decisions.